2019
DOI: 10.1001/jamasurg.2019.2884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Dose Supplementation of Arginine Vasopressin on Need for Blood Product Transfusions in Patients With Trauma and Hemorrhagic Shock

Abstract: IMPORTANCE Current therapies for traumatic blood loss focus on hemorrhage control and blood volume replacement. Severe hemorrhagic shock, however, is associated with a state of arginine vasopressin (AVP) deficiency, and supplementation of this hormone may decrease the need for blood products in resuscitation.OBJECTIVE To determine whether low-dose supplementation of AVP in patients with trauma (hereinafter referred to as trauma patients) and with hemorrhagic shock decreases their need for transfused blood prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 49 publications
0
78
0
1
Order By: Relevance
“…First, Sims et al recently showed that low-dose arginine vasopressin during the resuscitation of trauma patients in hemorrhagic shock decreased blood product requirements. 20 Unfortunately, the number of patients with concomitant TBI was small, and the effects on mortality are yet to be elucidated. Second, the use of tranexamic acid has been shown to reduce the mortality of trauma patients with significant hemorrhage when given in the initial 3 hours and has become a standard of the initial management of traumatic hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 99%
“…First, Sims et al recently showed that low-dose arginine vasopressin during the resuscitation of trauma patients in hemorrhagic shock decreased blood product requirements. 20 Unfortunately, the number of patients with concomitant TBI was small, and the effects on mortality are yet to be elucidated. Second, the use of tranexamic acid has been shown to reduce the mortality of trauma patients with significant hemorrhage when given in the initial 3 hours and has become a standard of the initial management of traumatic hemorrhagic shock.…”
Section: Discussionmentioning
confidence: 99%
“…52 Physicians, educators and policy-makers should have an awareness of the geographical, economic and staffing capacity of rural environments prior to instituting any telemedicine programme. 53 Rural physicians in our study viewed telemedicine as tool to enhance to the consultation process.…”
Section: Discussionmentioning
confidence: 86%
“…Current guidelines recommend the administration of vasopressors in addition to fluids to maintain target SBP in the presence of life-threatening hypotension [25,26]. Recent studies on the use of vasopressin in trauma patients with hemorrhagic shock are promising [32,33] but additional research is necessary to determine effect on morbidity or mortality. In addition to fluids and vasopressors, the prehospital activation of an intra-hospital standardized hemorrhage control response including a transfusion protocol is recommended [34,35].…”
Section: Discussionmentioning
confidence: 99%